STRATEGI KOMUNIKASI SATUAN LALU LINTAS (SAT LANTAS) KEPOLISIAN RESORT KOTA (POLRESTA) PEKANBARU DALAM MENSOSIALISASIKAN “SAFETY RIDING” - Harun Al Rasyid; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The level of traffic violations in Pekanbaru increasingly rising. Traffic violations consist of 21493 was given a speeding ticket and 6713 given a reprimand in 2014, whereas in 2015 increased significantly, namely; 11403 27 788 was given a speeding ticket and given a reprimand against violators of traffic in the city of Pekanbaru. In an effort to reduce abuse and raise public awareness of Pekanbaru in driving safe, orderly and peaceful course, is inseparable from the role of communication a more active and effective. The strategy used by the Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru include preventive strategy being pursued is to disseminate